Hepatic fascioliasis: case report and review Fasciolíase hepática. Relato de um caso e revisão da literatura - Salha Abdul-Hadi; Rosa Contretas; Claudio Tombazzi; Marta Alvarez; Maribel Melendez (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
A well documented case of hepatic fascioliasis (HF), successfully treated with triclabendazole, is reported. Predominant clinical manifestations were fever, marked eosinophilia and abdominal pain. Triclabendazole was given as two single oral doses of 10 mg/kg each. Neither side effects nor clinical or parasitological relapses were seen after three months of follow up Based on this experience and few other similar reports in the literature, triclabendazole might be a valid therapeutical alternative in the treatment of human fascioliasis. Os autores relatam um caso bem documentado de fasciolíase hepática (FH) tratado com êxito com triclabendazole. As manifestações clínicas predominantes foram febre, eosinofilia marcante e dor abdominal. Triclabendazole foi dado em duas doses únicas orais de 10 mg/kg cada. Não houve efeitos colaterais, nem recaídas clínicas ou parasitológicas até três meses após tratamento. Baseados nesta experiência e em outros poucos dados revistos na literatura, triclabendazole poderia ser uma alternativa terapêutica válida no tratamento da fasciolíase humana.